A secular Europe law and religion in the European constitutional landscape - Zucca, Lorenzo (Oxford : Oxford University Press, 2013)
The accommodation of diverse religious practices and laws within a secular framework is one of the most pressing and controversial problems facing contemporary European public order. In this title, Lorenzo Zucca develops a new picture of what secularism means and how Europe can reconcile its religious diversity.
Description based on online resource; title from PDF title page (viewed on Oct. 30, 2012).
Keywords: Constitutional law -- European Union countries; Constitutional law -- Religious aspects; Secularism -- European Union countries; Freedom of religion -- European Union countries; Cultural pluralism -- European Union countries